THE EFFECT OF PRODUCT PRICE AND PRODUCT QUALITY ON PURCHASING DECISIONS FOR SAMSUNG BRAND HANDPHONES AMONG STIE AAS SURAKARTA STUDENTS - Dewi Muliasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to analyze the mobile phone price towards the decision to purchase Samsung mobile phone among STIE AAS Surakarta students and to analyze the quality of the Samsung mobile phone product against the decision to buy a Samsung mobile phone among STIE AAS Surakarta students. The populationS in this study were all consumers or users of Samsung mobile phones among STIE AAS students. The sample in this study was Samsung mobile phone users as many as 100 respondents. The results of this study indicate that the t test results are known to significantly influence the price variable purchasing decisions. The results of the F test together with the price variable (X1) and product quality (X2) have a joint effect on purchasing decisions. R2 analysis results obtained adjusted R square (R2) of 0.0627 means that variations in changes in purchasing decision variables can be explained by nutrient variables (X1) and product quality (X2) have a positive effect on purchasing decisions by 62.8%. While, the remaining Values Of 37.2% is explained by other variables outside the model. Keywords: Price, product quality, buying decision, mobile phone.